SINYAL KEUANGAN DAN NILAI PERUSAHAAN : ANALISIS PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN SEKTOR FOOD AND BEVERAGE - Wachidah Fauziyanti; Ariyani Indriastuti (Sekolah Tinggi Ilmu Ekonomi Semarang, 2026)
This study aims to examine the effect of profitability, leverage, and firm size on firm value in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) for the 2022-204 period. By employing a purposive sampling method, a sample of 33 companies was selected, yielding a total of 99 observational data points over three years. The data analysis method used was multiple linear regression analysis processed via SPSS software. The descriptive statistical results showed an average profitability (ROA) of 0.0744, leverage (DER) of 0.3650, firm size of 22.4972, and firm value (PBV) of 0.0173. partial hypothesis testing indicated that profitability has a negative and insignificant effect on firm value. Meanwhile, leverage is proven to have a positive and significant effect on firm value. Simultaneously, these three independent variables explain 95.3% of the variation in firm value, while the remaining 4.7% is influenced by other variables outside this research model.